Old Boy Networks as Screening Mechanisms - Saloner, Garth (Journal of Labor Economics, 1985)
This paper studies a fulfilled-expectations equilibrium in situations in which intermediaries provide personal opinions on the likelihood of success of personnel, projects, or investments. Each referee must recommend some candidates from a group of people about whom he has private information. The employer uses the recommendations to choose the workers, using his expectations about the quality of the recommended and the nonrecommended applicants. Although the referees use their information strategically, the competition among them produces optimal use of the information in the sense that employers make the same choices in equilibrium as they would if they had the same information as the referees.